Determining Building Natural Ventilation Potential via IoT-Based Air Quality Sensors - Luo, Maohui; Hong, Yumeng; Pantelic, Jovan (Frontiers in Environmental Science, 2021)
Natural ventilation (NV) represents the most energy-efficient way to operate buildings and, in an attempt to reduce the built environment's global carbon footprint, represents a resource in which usage has to be maximized. This study demonstrates how a combination of an IoT environmental sensing network implemented locally outdoors and indoors can help to determine the NV potential and actual utilization throughout the year with the consideration of outdoor climate variance, air pollution levels, and window open/closed status. An NV potential index was developed by analyzing indoor and outdoor PM2.5, and outdoor air temperature and airspeed throughout the year at different spatial (from room-scale to building level and local weather stations) and temporal (instantaneous, season, and annual) scales. By applying the NV potential index to the case study building, we found that 61.2% of the time throughout the period of the study, conditions were favorable for NV usage. However, actual NV usage was only 35 % of the available potential. This result suggests that actual window use is the factor that restricts the most utilization of the available NV potential. Occupant behavior regarding keeping windows open or closed needs consideration during the planning and designing of the NV strategy. This result demonstrated that with the further development and adaptation of IoT sensing, we need to develop ways to communicate information to the occupants and use more available natural potential while improving the environment they use. The actual window usage behavior (open/closed status) was significantly affected by outdoor climate conditions and air pollution levels. Occupants kept windows open only while the outdoor temperature is neutral to warm and the air pollution level was low.